2013
DOI: 10.1254/jphs.12194fp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Chemical Chaperone 4-Phenylbutylate on the Function of the Serotonin Transporter (SERT) Expressed in COS-7 Cells

Abstract: Abstract. The serotonin transporter (SERT) is involved in various psychiatric disorders, including depression and autism. Recently, chemical chaperones have been focused as potential therapeutic drugs that can improve endoplasmic reticulum (ER) stress-related pathology. In this study, we used SERT-transfected COS-7 cells to investigate whether 4-phenylbutylate (4-PBA), a chemical chaperone, affects the membrane trafficking and uptake activity of SERT. Treatment with 4-PBA for 24 h dose-dependently increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Still, our data did indicate that PBA produces significant rescue in mild conditions that produce no toxic effects, both in COS7 cells and in cultured neurons. PBA increases GlyT2 transport activity and plasma membrane expression by fulfilling chaperone-like activity, as proven for other misfolded pathogenic proteins (44,51). PBA is an interesting compound because not only is it a chemical chaperone approved by the Food and Drug Administration for use in humans, but it can also pass across the bloodbrain barrier, and it has been implicated as a protective agent in neurodegenerative diseases involving ER stress (52).…”
Section: Discussionmentioning
confidence: 97%
“…Still, our data did indicate that PBA produces significant rescue in mild conditions that produce no toxic effects, both in COS7 cells and in cultured neurons. PBA increases GlyT2 transport activity and plasma membrane expression by fulfilling chaperone-like activity, as proven for other misfolded pathogenic proteins (44,51). PBA is an interesting compound because not only is it a chemical chaperone approved by the Food and Drug Administration for use in humans, but it can also pass across the bloodbrain barrier, and it has been implicated as a protective agent in neurodegenerative diseases involving ER stress (52).…”
Section: Discussionmentioning
confidence: 97%
“…Several groups revealed that 4-PBA reverses the mislocalization and/or aggregation of the protein associated with human disease, including the ΔF508 cystic fibrosis transmembrane conductance regulator [47], mutant α1-antitrypsin [70]. In addition, 4-PBA improves the trafficking of the serotonin transporter (SERT) [71], by reversing the misfolded proteins and decreasing the protein folding load in the ER, therefore providing protective effects against ER stress. A previous study has shown that 4-PBA treatment decreases ER stress with regard to the following general ER stress markers: BiP, CHOP, activating transcription factor 4 (ATF4), as well as sXBP1 [56].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism was postulated to be decreased trafficking to a functional position (Iwata et al, 2014). 4-phenylbutylate increased the trafficking of SERT in COS-7 cells, thus modulating its function and again lending credence to the endosomal system as a source for etiological and pharmacological intervention for ASDs (Fujiwara et al, 2013). Trafficking and cell surface expression dysfunction were also associated with SERT in ASDs in another study that used HeLa cells (Prasad et al, 2009).…”
Section: : Reviewmentioning
confidence: 95%